Strategi Structured Learning Approach (SLA) dalam Bimbingan Kelompok untuk Membentuk Self Awareness - Eko Yudi Susilo; IM Hambali; Muslihati Muslihati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Self-awareness is the ability to observe oneself, recognize feelings, and understand the relationship between thoughts, emotions, and how they influence each other. It involves knowing whether thoughts or feelings influence decisions, recognizing one's strengths and weaknesses, and being able to view oneself in a positive and realistic light. Self-awareness is an important element in personal development for students as it affects their mindset and behavior. This study aims to examine group counseling services with the Structured Learning Approach (SLA) strategy to develop self-awareness. The method used in this study is a Systematic Literature Review (SLR). The literature review found 30 scholarly works, but 10 articles were relevant to the research. Based on the review, it is predicted that group counseling using the Structured Learning Approach (SLA) strategy can help in developing students' self-awareness. This research can serve as a scientific foundation for the implementation of group counseling using the SLA strategy to develop students' self-awareness. It can also serve as a theoretical foundation for future research. The findings from the article review suggest that group counseling can enhance self-awareness. This study also calls for further research to examine whether there is an effect of the Structured Learning Approach (SLA) strategy in group counseling for developing students' self-awareness.